Supply Chain Risk Analysis With MAFMA Method Approach - Fatimah Fatimah; Indah Asmara; Sri Mutia; M Sayuti (International Journal of Engineering, Science and Information Technology, 2021)
Palm oil mill is a palm oil and palm kernel processing industry which is a semi-finished product. The palm oil industry is currently growing rapidly in line with the demand for large quantities of CPO and Kernal and their derivatives. In its operation, it is always faced with various risks, from the field to the processing plant. These risks will cause losses to the factory, especially in the form of financial. From the results of field observations obtained 13 kinds of supply chain risks, namely damaged trucks, FFB not up to standard, damaged FFB, insufficient FFB, network error, FFB damaged in the sorting field, boiling problems, problematic polisyndrom, abnormal steem, abnormal processes. /stops, viber cyclone plugs and leaks pipe. Therefore, it is necessary to identify, measure and manage risks to reduce losses caused by supply chain risks. The method used in this study is the MAFMA (Multi Attribute Failure Mode Analysis) method. The MAFMA method is a development of the FMEA method. The results showed that the risk level value contained 4 critical risks on the part of the factory, namely FFB less with a risk level value of 0.096, FFB not according to standards with a risk level value of 0.085, network error with a risk level value of 0.083 and the process running abnormally. /stop with a risk level of 0.073. These 4 critical risks are the priority to be handled. The handling carried out is planning for the right FFB procurement, providing guidance on the harvesting process, stabilizing the network by providing copper rods and planning machine scheduling.